Handbook of Forensic Pathology - DiMaio, V. J. M. Vincent J. M (Taylor and Francis, 2007)
Handbook of Forensic Pathology, Second Edition is an up-to-date, concise manual illustrating all core aspects of modern forensic pathology. This edition retains the outline format of the original, which allows for quick access and rapid assimilation. Written in no-nonsense, easily understandable language, this precise and thorough yet compact resource contains extensively detailed entries from two of the nation's foremost authorities on gunshot wounds and forensic pathology. With numerous instructional charts and diagrams and color photographs, it organizes a wealth of instructional and immediately applicable information. Features of the second edition include a chapter on nursing home death, added information on gunshot residue, and research on tasers, pepper spray, and excited delirium syndrome. Introducing medicolegal casework and documentation, this book explains protocols for the collection and recovery of evidence and DNA analysis and lists factors used to determine time of death and identity of the deceased. It identifies the natural causes of death in children and adults before devoting the remaining chapters to the myriad of non-natural causes including homicide, suicide, accidental, and undetermined. With meticulous detail and instant access to extensive information, this handbook is an indispensable tool for forensic pathologists, law enforcement, and legal personnel, as well as pathologists in training.